Too Much Light: The Art of the Hero’s Journey (Photo Essay) - Adler, Karen (The international journal of religious tourism and pilgrimage, 2020)
We live in an age in which spiritual searching and seeking is more common, particularly among the youth. The need for answers and solutions to a world in danger of dying, of a society in which corruption and decay are so transparently obvious, leads many on paths which are dangerous and uncharted. The metaphor of journey, the practice of pilgrimage, the art of navigation, all contain the notion of process and movement rather than stagnation. They provide us with tools to not only emerge whole from experiences which have the power to break and shatter us but to provide maps for others to use. The title, ‘Too Much Light: The Art of The Hero’s Journey’, reflects the experience of Spiritual Crisis of both Karen Adler and Teresa McLaren. This phenomenon is little known in Western society and is most easily understood as an extreme emotional state with symptoms such as loss of contact with consensual reality, delusions and hallucinations which are similar to those labelled psychosis (Grof & Grof, 1989; Phillips et al. 2009). Stories of Too Much Light, becoming lost and ultimately finding one's way back to health, happiness and sanity via the arts and The Hero’s Journey archetype, are shared by many in the world today. It is a common initiation story in very disparate cultures and among very different individuals. The commonalities of these stories serve to illustrate the underlying connectedness of who we are as human beings. Stories and artworks by those who have survived these experiences encourage others to listen to and benefit from the deep wisdom, beauty and strength that reside in all of us. We hope that lay people, academics and members of the mental health professions will use this resource as a source of explanation and understanding for experiences which are deeply disturbing, quite often terrifying but ultimately life-enhancing. Marie Grace Brook writes that knowing about these experiences have ‘Implications for spiritual tourism and pilgrimage … both for the purpose of supporting people in their spiritual[ly] transformative journeys, and for normalizing characteristic extreme states mimicking psychosis that potentially accompany powerful spiritual experience’ (Brook 2020:1).